Heart Failure Pharmacotherapy: Differences Between Adult and Paediatric Patients - Bajcetic, M.; Vidonja Uzelac, T.; Jovanovic, I. (Current Medicinal Chemistry, 2014)
During the last decades, the introduction of new, more efficient drugs, has significantly improved the heart failure (HF) therapy of adults. Therapeutic focus has shifted from simple hemodynamic manipulation to include neurohumoral modulation as a consequence of the better understanding of mechanisms of HF formation, in particular at the cellular level. The aetiologies of HF in children are remarkably different and more varied than in the adult population. Cardiac failure is usually caused by congenital heart disease and cardiomyopathy in children, whereas in adults, coronary artery disease, hypertension and myocardial infarction are the most common causes. Despite this fact, pharmacotherapy of children is based on the same drugs, usually extrapolated from adult HF regimens. A recently published study in children treated with the drugs known to be efficient in adult HF therapy, provides encouragement that the outcomes might be similarly beneficial. On the other hand, some reports outline that children with HF, especially patients with systemic right ventricles or single ventricle physiology, require specific drug guidelines. A general characteristic of HF pharmacotherapy in children is the lack of paediatrically designed drugs. Drugs currently used in the treatment of HF in paediatric patients are designed for adults, and their efficacy, safety and quality have generally not been confirmed by clinical studies of children. Aside from this, availability of commercial paediatric drug formulations labelled for treatment of HF in children significantly influences the quality and efficacy of therapy.
Keywords: Clinical studies